R848 Adjuvant Laden With Self-Assembled Nanoparticle-Based mRNA Vaccine Elicits Protective Immunity Against H5N1 in Mice - Zhuang, Xinyu; Chen, Luer; Yang, Songhui; Xia, Shengnan; Xu, Zhiqiang; Zhang, Tong; Zeng, Boyu; Yu, Tong; Yu, Ning; Wang, Wei; Lu, Huijun; Tian, Mingyao; et al. (Frontiers in Immunology, 2022)
In order to perfect the design strategy of mRNA vaccines against H5N1 influenza virus, we investigated whether different antigen designs and the use of adjuvants could improve the immune effect of mRNA vaccines. We designed three different forms of antigen genes, including Flu (H1/H3/H5/B-HA2(aa90~105)-M2e(24aa)), Flu-Fe (Fe, ferritin) and CD5-Flu-Fe (CD5, a secretion signal peptide). Meanwhile, R848 (Requimod) was selected as the adjuvant of mRNA vaccine. We prepared a cationic lipid nanoparticles for mRNA delivery, named LNP-Man (Mannose-modified lipid nanoparticles). Cell transfection results showed that Flu-Fe/CD5-Flu-Fe containing ferritin could express the target antigens HA2 and M2e more efficiently than Flu. In the mice immune experiment, five immune groups (LNP-Man/Flu, LNP-Man/Flu-Fe, LNP-Man/CD5-Flu-Fe, LNP-Man/Flu-Fe+R848, and LNP-Man/CD5-Flu-Fe+R848) and two control groups (LNP-Man, PBS) were set up. After being infected with 1×LD50 H5N1 avian influenza virus, the survival rate of the mice in the LNP-Man/CD5-Flu-Fe, LNP-Man/Flu-Fe+R848, and LNP-Man/CD5-Flu-Fe+R848 were 100%. More importantly, in LNP-Man/Flu-Fe+R848 and LNP-Man/CD5-Flu-Fe+R848 groups, there was no residual virus detected in the mice lung tissue on the 5th day post challenge. Overall, this study provides a new idea for the design of H5N1 avian influenza virus mRNA vaccines in terms of antigen designs and adjuvant selection.